Pressupostos epistêmicos para uma teoria ontológica do direito: em busca da verdade e do real na totalidade jurídica material - Bandeira, Joao Adolfo Ribeiro (2020)
The present doctoral work has as its object an ontological analysis of the legal phenomenon, having as a thesis the existence of epistemological assumptions capable of allowing the perspective of a theorization about an ontology of Law. Unlike other analyzes, it seeks to understand beyond the central question what Law is, the way it is built and carried out in the social sphere, that is, how Law is - thought as a central issue. To this end, the studies of Georg Wilhelm Friedrich Hegel, Imannuel Kant, Nicolai Hartmann, and, about the theory of modal categories, the analysis of Law from a dialectic of the real and about the true, respectively, in reference to contemporary analyzes of the Law as a prescription and description and an ontology while thought from a materialistic project. In this sense, the real and concrete condition of the Law is mitigated in axiological determinations, in different legal forms and contents and, finally, in innumerable conceptions that reflect the epistemic and ontological void of this theme. The starting hypothesis raised and which is reflected in the initially proposed thesis is defined in the relation of the productive and transforming forces of reality, both through the ontological alienation (axiological reduction) established and allowed as natural for the construction of being, although, for the Law, the recognition of these productive forces is itself impaired, since the legal phenomenon brings together its own apprehensions of other facts (social political,economic,etc.). In order to discuss theoretical understandings and categories of philosophical-legal knowledge, the present research uses the literature review as a research technique because it composes the vastness meeting about the premises raised to solve the problem, as a method of historical procedure, for allowing understanding about the facts and the intellectual production of the stages of legal and philosophical thought and as a method of approaching the dialectic-materialist, for being able to expose the contradictions existing in Law.